PEMBINAAN KEPEMIMPINAN PEMUDA MELALUI KETERAMPILAN PUBLIC SPEAKING DI PAC GP ANSOR SAGULUNG KOTA BATAM - Dompak, Timbul; Purwanti, Angel; Abidin, Sholihul; Wong, Angeline; Chaliza, Euis; Handini, Vernanda; Saleha, Vila Mas Masiana; Nova, Rahma Desi Refli (PUAN INDONESIA, 2024)
The Ansor Youth Movement (GP) is a youth, community, national, and religious organization with a popular character. The spirit of struggle, nationalism, liberation, and heroic ethos colors GP Ansor. GP Ansor has a vision, mission, and goals as a structured organization. GP Ansor has spread throughout all regions in Indonesia, including in Batam. The coaching at GP Ansor Sagulung District is carried out with the following stages of coaching: GP Ansor Youth follows all the material that will be delivered at this coaching activity, namely: Organization and Leadership, Public Speaking, and Presentation Techniques. The methods to solve problems offered by the devotees are lectures and hands-on practice and ensuring that all GP Ansor youth understand the material presented, are given time to discuss, and can make presentations and speak in front of crowds in real situations.